1995
DOI: 10.3354/meps122009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of bacterioplankton biomass and production in the marginal ice-edge zone of the Weddell-Scotia Sea during austral winter

Abstract: Recent investigations in the marginal ice-edge zone (MIZ) of the western Weddell and Scotia Seas revealed similar distributions of primary and microbial production in spring and autumn. Yet, little is known about the distributions of bacterial biomass and production in winter, and how these distributions may be influenced by local physical oceanographic features or interrelated to other chemical and biological distributions in the M1Z. To help elucidate the ecological and biogeochemical significance of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…In general, our observations agree with findings about a higher invariance of bacterioplankton compared to phytoplankton in winter and during ice melt (e.g. Cota et al 1990, Becquevort et al 1992, Mordy et al 1995. Surprising, however, is our observation that the precence of (herbivorous) mesozooplankton even intensifies these shifts in community composition.…”
Section: Resultssupporting
confidence: 92%
“…In general, our observations agree with findings about a higher invariance of bacterioplankton compared to phytoplankton in winter and during ice melt (e.g. Cota et al 1990, Becquevort et al 1992, Mordy et al 1995. Surprising, however, is our observation that the precence of (herbivorous) mesozooplankton even intensifies these shifts in community composition.…”
Section: Resultssupporting
confidence: 92%
“…Several comprehensive studies of Antarctic bacterioplankton have been performed, yet there is little agreement on the principal factors regulating bacterial growth (Ducklow et al 2001), and very few of these studies encompass winter (Mordy et al 1995, Scott et al 2000. This study found large seasonal variation in bacterioplankton abundance in Antarctic coastal waters that correlated with seasonal changes in the physical and biological environment.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, during winter in the Antarctic, Helmke & Weyland (1995) found very low bacterial production beneath the pack ice. In contrast, Mordy et al (1995) found that bacterial production in water near the ice margin during winter was equivalent to 44% of primary production. This bacterial activity in winter likely reflects the fact that there is some year-round phytoplankton photosynthesis in most of the Southern Ocean, and it is enhanced near the ice edge even in winter (Cota et al 1992).…”
Section: Permanently Cold Watersmentioning
confidence: 70%
“…They include many measurements in water and sediments with an annual temperature range ≤ 4°C. Bacterial metabolic activity in polar waters in winter in the marginal ice zone is sometimes similar to that of summer (Rivkin et al 1989, Mordy et al 1995. In other instances very low rates are seen, although little seasonal temperature change occurred (Griffiths et al 1978, Pomeroy et al 1990, Karl 1993, Carlson et al 1998, Bird & Karl 1999.…”
Section: Permanently Cold Watersmentioning
confidence: 99%